Взаємодія інформації та робототехнічної системи - Pentiuc, S. G.; Vatavu, R. D.; Ungurean, O. C.; Laurent, G.; Christophe, C.; De Backer, L.; De Strycker, L.; Hamburg, I. (Vinnytsia National Technical University, 2013)
The aim of this paper is to present the results obtained during the project 131-CEEX/2006, INTEROB: Interacting by Gestures with Information and Robotics Systems for the time frame 2006-2008. The project focused on natural interaction using gesture recognition technology applied in various applications such as: virtual environments, augmented reality, collaborative working and interaction with robotics systems.